JEJARING FARMAKOLOGI DAUN UBI JALAR (Ipomoea batatas L.) SEBAGAI PENYEMBUHAN LUKA BAKAR - Tri Diana Puspita Rini; Wa Ode Fefen Nurmalah (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2026)
Burns are complex tissue injuries involving inflammation, oxidative stress, and cell death, requiring effective and safe therapy. Sweet potato leaves (Ipomoea batatas L.) are known to contain bioactive compounds such as flavonoids and polyphenols, which have potential as wound healing agents. This study aims to identify the molecular mechanisms of active compounds from sweet potato leaves in burn wound healing using a network pharmacology approach. The research methods included identification of active compounds through the KNApSAcK database and literature, structure verification using PubChem, and drug-likeness analysis using SwissADME based on Lipinski’s rules. Protein target prediction was performed using SwissTargetPrediction, while disease targets were obtained from GeneCards. Protein-protein network analysis (PPI) was performed using STRING and visualization with Cytoscape. Gene Ontology and KEGG pathway analysis were then performed. The results showed 29 active compounds with 231 target proteins that overlapped with burn injury genes. Topological analysis identified key proteins such as STAT3, IL6, AKT1, and CASP3. GO and KEGG analyses revealed the involvement of inflammatory pathways, oxidative stress, and tissue proliferation and regeneration. These findings suggest that sweet potato leaves have potential as a burn wound healing agent through an integrated multi-target mechanism.